Patient-reported continuous clinical response to golimumab in adults with moderately to severely active ulcerative colitis: results from GO OBSERVE, a real-world European observational study. Issue 6 (8th April 2022) - Ferrante, Marc; Schirbel, Anja; Pierik, Marieke J.; Haas, Thomas; Flamant, Mathurin; Khalifa, Ahmed; Philip, George; Cornillie, Freddy; Meehan, Alan G.; Govoni, Marinella
Abstract : Background: In PURSUIT, golimumab (GLM) was efficacious in patients with moderate-to-severe ulcerative colitis (UC). We assessed whether remote monitoring of combined patient-reported Mayo stool frequency and rectal bleeding scores is an effective real-world outcome measure for assessing maintenance of GLM-induced clinical response. Methods: This was a 54-week prospective, observational cohort study conducted at 43 European outpatient clinics in adults with moderate-to-severe UC who were biologic naïve or had received a maximum of one other biological therapy. Patients were treated according to European GLM UC label/local practice. Clinical response (based on partial or full Mayo score) was assessed at week 6, 10, or 14 of induction, depending on local practice. Investigators remotely monitored scores every 4 weeks. The primary endpoint was the proportion of induction responders in patient-reported continuous clinical response (pCCR) at week 54, defined as absence of UC flare based on combined patient-reported Mayo stool frequency and rectal bleeding scores every 4 weeks and full or partial Mayo score. A key secondary endpoint was the proportion of induction responders in clinical remission at week 54. Results: Among 109 patients, 37 (34.0%) received at least two GLM induction doses and completed induction in clinical response (induction responders). At week 54, 15/37 (40.5%) induction responders were in pCCR, and 21/37 (56.8%) were in clinical remission. Conclusion: In daily clinical practice, regular remote monitoring of combined patient-reported Mayo stool frequency and rectal bleeding scores appears to be a meaningful real-world outcome measure for monitoring maintenance of GLM-induced clinical response in UC.